Research progress on microRNA in gout - Xie, Jing; He, Cuixia; Su, Yue; Ding, Yuzhou; Zhu, Xingyu; Xu, Yuanyuan; Ding, Jiaxiang; Zhou, Huan; Wang, Hongju (Frontiers in Pharmacology, 2022)
Gout is a common form of arthritis caused by the deposition of sodium urate crystals in the joints and tissues around them. MicroRNAs (miRNAs) are noncoding RNAs that have been shown to be involved in regulating the pathogenesis of gout through multiple cellular signaling pathways, which may be potential targets for the treatment of gout. In this review, we systematically discuss the regulatory roles of related miRNAs in gout, which will provide help for the treatment of gout and miRNAs is expected to become a potential biomarker for gout diagnosis.